Apresentação do Dossiê "As intelectualidades negras na compreensão do Brasil" - Oliveira , Fernanda; Gomes , Marília Passos Apoliano; Lira, Bruno Ferreira Freire Andrade (PerCursos, 2024)
Apresentação do Dossiê "As intelectualidades negras na compreensão do Brasil"